A confusion of princes - Nix, Garth (HarperTeen, 2012)
"Battling aliens, space pirates, and competitors, Prince Khemri meets a young woman, named Raine, and learns more than he expected about the hidden workings of a vast, intergalactic Empire, and about himself"--